Polymer dispersed ionic liquid electrolytes with high ionic conductivity for ultrastable solid‐state lithium batteries - Shengyu Qin; Yaping Cao; Jianying Zhang; Yunxiao Ren; Chang Sun; Shuoning Zhang; Lanying Zhang; Wei Hu; Meina Yu; Huai Yang (Carbon Energy, 2023)
Abstract Solid polymer electrolytes (SPEs) have emerged as one of the most promising candidates for building solid‐state lithium batteries due to their excellent flexibility, scalability, and interfacial compatibility with electrodes. However, the low ionic conductivity and poor cyclic stability of SPEs do not meet the requirements for practical applications of lithium batteries. Here, a novel polymer dispersed ionic liquid‐based solid polymer electrolyte (PDIL‐SPE) is fabricated using the in situ polymerization‐induced phase separation (PIPS) method. The as‐prepared PDIL‐SPE possesses both outstanding ionic conductivity (0.74 mS cm−1 at 25°C) and a wide electrochemical window (up to 4.86 V), and the formed unique three‐dimensional (3D) co‐continuous structure of polymer matrix and ionic liquid in PDIL‐SPE can promote the transport of lithium ions. Also, the 3D co‐continuous structure of PDIL‐SPE effectively accommodates the severe volume expansion for prolonged lithium plating and stripping processes over 1000 h at 0.5 mA cm−2 under 25°C. Moreover, the LiFePO4//Li coin cell can work stably over 150 cycles at a 1 C rate under room temperature with a capacity retention of 90.6% from 111.1 to 100.7 mAh g−1. The PDIL‐SPE composite is a promising material system for enabling the ultrastable operation of solid‐state lithium‐metal batteries.